PENGARUH KUALITAS AUDIT TERHADAP KEPUASAN KLIEN - Mika Marsely Mika Marsely (Jurnal Ekonomi dan Bisnis Airlangga, 2017)
The purpose of this research is to examine the effect of audit quality on client satisfaction. The unit of analysis in this study is the PNPM Mandiri Urban LKM in Sidoarjo Regency, amounting to 291 MFIs scattered in all villages / wards in Sidoarjo Regency. PNPM Mandiri Urban LKM is a nonprofit organization that aims to alleviate poverty. The sample in this study consisted of 32 economic village village (faskel) facilitators who overshadowed 291 LKM and also acted as counterpart auditors during the audit. The number of questionnaires distributed was 32 copies and 32 returned questionnaires or as many as 100%. The data analysis technique used in this research is Multiple Linear Regression Analysis.The results of this study indicate that the understanding attribute of the client industry and responsiveness to client needs has a significant effect on client satisfaction. Meanwhile, the attributes of competence, independence, caution of the audit team, KAP commitment to quality, high ethical standards and skepticism of the audit team did not have a significant effect on client satisfaction. The limitation in this study is that the sample used only comes from one party, namely the auditee. It is recommended that further research should use samples from both parties between the auditee and the auditor so that more valid answers can be obtained